Antigen-driven T cell-macrophage interactions mediate the interface between innate and adaptive immunity in histidyl-tRNA synthetase-induced myositis - Reay, Daniel P.; Tabib, Tracy; Wang, Ying; Oriss, Timothy B.; Young, Nicholas A.; Lafyatis, Robert A.; Jarjour, Wael N.; Clemens, Paula R.; Ascherman, Dana P. (Frontiers in Immunology, 2023)
Previous work in humans has demonstrated that both innate and adaptive immune signaling pathways contribute to the pathogenesis of idiopathic inflammatory myopathy (IIM), a systemic autoimmune disease targeting muscle as well as extra-muscular organs. To better define interactive signaling networks in IIM, we characterized the cellular phenotype and transcriptomic profiles of muscle-infiltrating cells in our established murine model of histidyl-tRNA synthetase (HRS)-induced myositis. Myositis was induced in wild type (WT) and various congenic/mutant strains of C57BL/6 mice through intramuscular immunization with recombinant HRS.Histopathological, immunohistochemical, flow cytometric, and transcriptomic assessments were used to characterize the functional relationship between muscle-infiltrating cell populations in these strains lacking different components of innate and/or adaptive immune signaling. RAG1 KO mice developed markedly reduced muscle inflammation relative to WT mice, demonstrating a key requirement for T cells in driving HRS-induced myositis. While the reduction of mononuclear cell infiltrates in CD4-Cre.MyD88 fl/fl conditional knockout mice and OT-II TCR transgenic mice highlighted roles for both innate and TCR-mediated/adaptive immune signaling in T cells, diminished inflammation in Lyz2-Cre.MyD88 fl/fl conditional knockout mice underscored the importance of macrophage/myeloid cell populations in supporting T cell infiltration. Single cell RNA sequencing-based clustering of muscle-infiltrating subpopulations and associated pathway analyses showed that perturbations of T cell signaling/function alter the distribution and phenotype of macrophages, fibroblasts, and other non-lymphoid cell populations contributing to HRS-induced myositis. Overall, HRS-induced myositis reflects the complex interplay between multiple cell types that collectively drive a TH1-predominant, pro-inflammatory tissue phenotype requiring antigenmediated activation of both MyD88-and TCR-dependent T cell signaling pathways.